Determinan Penyakit Kulit pada Pemulung di TPA Telaga Punggur - Zahara Gema Gatra; M. Kafit; Herdianti Herdianti (Jurnal Kesehatan Manarang, 2021)
Dermatitis is a disease that attacks the skin on the surface of the body which is commonly found among residents in hot, humid climates, poor personal hygiene, poor environment, and workers who deal with dirt (e.g. garbage and sewers). This study aimed to determine the relationship between personal hygiene and the use of PPE for scavengers with skin diseases at the TPA Telaga Punggur, Batam City. The method used was descriptive quantitative using a cross-sectional study design. The population in this study were all scavengers in TPA Telaga Punggur as many as 791 scavengers and as many as 89 scavengers who were sampled by purposive sampling technique. The results showed that 75.3% had poor personal hygiene and 73.0% did not wear PPE when working, and 70.8% had skin diseases. There is a relationship between personal hygiene (p = 0.006) and the use of PPE (p = 0.000) with the incidence of skin disease at Telaga Punggur landfill. Scavengers are expected to pay attention to clean and healthy living behavior by maintaining personal hygiene and always using personal protective equipment when working.